2022
DOI: 10.3390/ijerph19127142
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Lockdown Policies in the Pre-Vaccine Era of COVID-19: A Configurational Perspective

Abstract: The significance of lockdown policies for controlling the COVID-19 pandemic is widely recognized. However, most studies have focused on individual lockdown measures. The effectiveness of lockdown policy combinations has not been examined from a configurational perspective. This research applies fuzzy-set qualitative comparative analysis (fsQCA) to examine different lockdown policy combinations associated with high-epidemic situations in 84 countries. A high-epidemic situation can occur through three different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…In 2021, Chinese epidemic prevention and control policies were based on the general strategies of "defending externally against importation, defending internally against rebound" and "dynamic zero-case" policy [40]. Therefore, mental health problems (such as anxiety and depression) are likely to have arisen as direct results of, for example, blocked access, frequent nucleic acid testing and fewer outings [41,42]. Several studies have shown COVID-19 related anxiety to be associated with psychiatric health problems among adults with uncommon disorders and that the prevalence of anxiety has been higher during the pandemic than before the pandemic [43].…”
Section: Increases In the Incidence Of Bullying Victimization And Per...mentioning
confidence: 99%
“…In 2021, Chinese epidemic prevention and control policies were based on the general strategies of "defending externally against importation, defending internally against rebound" and "dynamic zero-case" policy [40]. Therefore, mental health problems (such as anxiety and depression) are likely to have arisen as direct results of, for example, blocked access, frequent nucleic acid testing and fewer outings [41,42]. Several studies have shown COVID-19 related anxiety to be associated with psychiatric health problems among adults with uncommon disorders and that the prevalence of anxiety has been higher during the pandemic than before the pandemic [43].…”
Section: Increases In the Incidence Of Bullying Victimization And Per...mentioning
confidence: 99%
“…At the beginning of an outbreak of a highly transmissible infectious disease such as COVID-19, the primary focus is on containing its spread through measures such as city lockdowns while effective vaccines or treatments are still in development ( 1 , 2 ). Previous studies have shown that these containment measures can be effective in slowing the spread of the disease and reducing transmission ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%